Associations among behavioral and psychological symptoms of dementia, care burden, and family‐to‐work conflict of employed family caregivers. Issue 1 (16th December 2018) - Sakka, Mariko; Goto, Jun; Kita, Sachiko; Sato, Iori; Soejima, Takafumi; Kamibeppu, Kiyoko
Abstract : Aim: The present study aimed to examine the associations among behavioral and psychological symptoms of dementia (BPSD) of persons with dementia (PWD), care burden and family‐to‐work conflict (FWC) of employed family caregivers. Method: A cross‐sectional study was carried out with employed adult daughter or son (or in‐law) caregivers for PWD from two rural cities in Japan. FWC, care burden and the degree of BPSD were evaluated by the Survey Work‐Home Interaction‐NijmeGen, Zarit Burden Scale‐Short Version and Dementia Behavior Disturbance Scale, respectively. Of the 200 questionnaires distributed, 130 were returned. A total of 53 respondents were not employed, and seven questionnaires had missing data for demographic variables, Survey Work‐Home Interaction‐NijmeGen, Zarit Burden Scale‐Short Version or Dementia Behavior Disturbance Scale. Thus, complete data from 70 respondents were analyzed through structural equation modeling. Results: The mean age of employed family caregivers was 56 years, and 34 (48.5%) were men. The mean age of PWD was 84 years, and there were 68 (68.6%) men. The path model with a good fit was shown (root mean square error of approximation 0.136, comparative fit index 0.960 and goodness of fit index 0.965). The path model showed that BPSD affected FWC, and that the association was partially mediated by care burden. Conclusions: The results show that a decrease in not only care burden, but also BPSD, of PWD is important for employed family caregivers to reduce their FWC and maintain their work–life balance.Geriatr Gerontol Int 2019; 19: 51–55 .